CULTURAL ADAPTATION IN CHARACTER EDUCATION: SUNDANESE LITERATURE-BASED COMICS IN THE JABAR MASAGI PROGRAM - Nasution, Shinta; Firdaus, Shofiyah Jannatul; Widyatami, Anindita (Jurnal Penelitian Kebijakan Pendidikan, 2025)
This study examines the role of comics based on ancient Sundanese literature as a medium for character education within the Jabar Masagi program. Manga, or Japanese comics, are often considered an effective form of character education media, and this study adapts that format using local cultural content. A quasi-experiment with a 2 x 1 factorial design, based on message type (positive and negative), was conducted with 66 students divided into two treatment groups and 33 students in a control group. Student members of the Japan Smavo Japanese Club participated in the comic development process to ensure cultural relevance. Results indicate that Jabar Masagi comics with negative messages significantly improved students’ knowledge, attitudes, and perceptions of noble values, whereas comics with positive messages did not enhance perceptions. Increases in knowledge, attitudes, and perceptions were also influenced by familiarity, interest, and family environment supportive of character education. The West Java Provincial Government is advised to integrate comics based on local wisdom into the Jabar Masagi program through participatory approaches and broad dissemination to strengthen contextual and sustainable character internalization.